Uma análise da trajetória das artes de governar no pensamento de Michel Foucault - MENEZES, Leandro Alves Martins de (2011)
This study aims to analyze the problems of life of the governments at the thought of Michel Foucault, between the years 1974 and 1979, especially around the invention, development and mapping of concepts and biopolitics anatomopolitics. For this, the development of our research starts from a careful analysis of the origins of life of the governments in association with the pastoral power with the birth and development of political economy. It is assumed in this sense, the attempt to introduce the reader to the historian Foucault. A philosopher historian who prepared his knowledge as a producer of motion, as inexhaustible, therefore, not feasible formulas of the past.